Woody plant encroachment drives habitat loss for a relict population of a large mammalian herbivore in South America - Cuellar-Soto, Erika; Johnson, Paul J.; Macdonald, David W.; Barrett, Glyn A.; Segundo, Jorge (THERYA, 2020)
Woody plant encroachment (WPE) is reshaping the physiognomy of grasslands and savannahs worldwide. At the same time, this habitat conversion is accelerating the loss of associated biodiversity. In general, studies on WPE have focused on abiotic factors, singly or in combination, that trigger this phenomenon. Despite its ecological relevance, very few studies have tackled the effects of WPE-spurred habitat transformation on animal species dependent on relatively open areas such as grasslands and savannas for survival. We studied a relict and almost extinct population of large, herbivorous guanacos (Lama guanicoe) in the Gran Chaco region, Santa Cruz department, Bolivia. We tested whether guanacos were using habitats (at particular and distinct stages of WPE) in relation to their availability. Although this species is considered a generalist herbivore. We tested variation in habitat use focusing on two spatial scales. First, at the landscape level, we performed aerial surveys. Second, at the fine scale, we tracked six groups of guanacos for twenty months and documented the various habitats used within their approximate home ranges. At both scales, we performed a Manly-Chesson’s index referring to the standardised proportional use of each habitat divided by the proportional availability of each, with the values for all habitats summing to 1. An index value < 1 or > 1 suggests, respectively, that a habitat is avoided or selected. We found a disproportionate use of open vegetation (scrubland and grassland) by guanacos in relation to habitat availability at both scales. In addition, the current distribution range of the species is restricted to less than 800 km2 of the approximately 3,000 km² potentially available in 1998. We confirmed a contraction between 1996 and 2006 in the distribution of the local Chacoan guanaco population from the area where guanacos were first monitored towards the Kaa-Iya National Park border. Our results showed that guanacos are restricted to relatively open areas. Furthermore, the observed reduction in the area previously occupied by the species could be the beginning of a distributional shift and potential loss of the guanaco’s geographic range due to habitat replacement. The latter was also reflected in a previous dietary study of this population we found that guanacos largely consumed the native grass A. mendocina (Poaceae), which has shrunk in distribution by 90 % in this region over a 40 year period and is gradually being replaced by an invasive forb, Lippia sp. Therefore, if the overall purpose on evaluating habitat use is to understand the basic requirements to sustain this population of guanacos, we need to highlight the poor quality and acute regression of the current preferred habitat. In this case, habitat structure can have a profound effect on the success of the guanaco population recovery and its long-term establishment. Therefore, we urge researchers and decision makers to look beyond the more direct human-induced pressures on the species, such as hunting, competition with domestic livestock and agricultural development and consider the importance of WPE as a direct driver for habitat loss.